2016
DOI: 10.1515/sjecr-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Doses of Nandrolone Decanoate on Cardiac Muscle Tissue

Abstract: In recent decades, steroid abuse has become very popular and widespread among professional and recreational athletes. The aim of this study was to examine the chronic effects of training combined with high doses of nandrolone decanoate on cardiac muscle tissue. The study included 32 Wistar albino rats divided into 4 groups: control (T-N-), steroid (T-N+), exercisetraining (T+N-) and exercise plus steroid (T+N+) groups. The T+N- and T+N+ group swam for 4 weeks, 1 hour per day, 5 days per week. The N+ (nandrolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
6
12
0
Order By: Relevance
“…Given that most parts of the heart wall consist of heart muscle cells, the findings of this study are consistent with the results of measuring cell diameter in a research by Sretenovic et al (2016) who confirm these findings (44). Ren et al (2012) also found that nandrolone induces heart hypertrophy (44). Overall, the present study demonstrates the side effects of androgenic steroid of boldenone on the heart morphology.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Given that most parts of the heart wall consist of heart muscle cells, the findings of this study are consistent with the results of measuring cell diameter in a research by Sretenovic et al (2016) who confirm these findings (44). Ren et al (2012) also found that nandrolone induces heart hypertrophy (44). Overall, the present study demonstrates the side effects of androgenic steroid of boldenone on the heart morphology.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, reduction of heart damage after heart intoxication was observed after Lcarnitine supplementation combined with exercise activities. Researchers have confirmed that the steroids, with or without training, influence the thickness of the heart with a dose-dependent method, but they have often examined the effects of high doses (from 1 to 10 mg/kg/week) on the heart (9,15,21,22,44). However, due to the lack of similarity in dose of anabolic-androgenic steroids, training programs and duration of experimental treatment in various studies, it is difficult to draw strong conclusions about the real effects of specific doses of steroids on the heart tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies showed that the administration of ААSs leads to the hypertension development [3], hypertrophy of the left ventricle, accumulation of extracellular collagen in both cardiac [4,5] and skeletal muscle [6] and hepatocellular damage [7]. Administration of ААSs has deleterious effects on testicles manifested as structural changes of the seminiferous epithelium [8] and testicular atrophy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is characterized by low hepatotoxicity, although results of previous studies indicated the role of the misuse of AASs in structural and functional changes of the liver (including the hepatocellular carcinoma) (Frankenfeld et al, 2014). Misuse of AASs may also cause left ventricular hypertrophy with a disproportional accumulation of extracellular collagen and consequential fibrosis (Tanno еt al., 2011; Hassan & Kamal, 2013; Sretenovic et al, 2016). Administration of AASs in high doses can cause a certain degree of testicular atrophy (Naraghi et al, 2010; Mohamed & Mohamed, 2015; Takahashi et al, 2004), ultrastructural changes in the testicles (Rocha et al, 2007), and lower circulating testosterone levels but can also affect the hypothalamic–pituitary–gonadal axis (HPG axis), in the sense of lowering the follicle-stimulating hormone (FSH) levels and the luteinizing hormone (LH) levels (Nagata et al, 1999; Naraghi et al, 2010; Ferrari et al, 2013; Mohamed & Mohamed, 2015; Shahraki et al, 2015; Takahashi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%